Impact of Low Salinity on Survival and Growth of Juvenile Mangrove Red Snapper (Lutjanus argentimaculatus Forsskål, 1775) in Indoor Tanks - Arkronrat, Wasana; Oniam, Vutthichai; Sangsawang, Akkarasiri; Aranyakanont, Chak; Prachom, Noratat; Konsantad, Rungtiwa (Journal of Fisheries and Environment, 2024)
Mangrove red snapper (Lutjanus argentimaculatus Forsskål, 1775) is a high-value marine fish and an ideal mariculture species. As a euryhaline species, it requires a deeper understanding of optimal cultivation conditions. This study examined the effects of different low salinity levels [20‰, 10‰, and 0‰ (freshwater)] on fish survival (SR) and growth of juvenile red snapper in indoor tanks, with fish reared in seawater (30‰) serving as a control. Fish were fed with commercial marine fish feed (42% protein) for six weeks. Results showed no significant (p≥0.05) differences in survival rates among salinity levels (0–20‰), with survival rates ranging from 95.00–100%, similar to 30‰ (100% SR). The final total length ranged from 9.20–9.55 cm across treatments, with no significant differences. However, fish reared at 20‰ had a significantly higher final body weight (37.43 g) than those at 30‰ (25.06 g), 10‰ (32.42 g), and 0‰ (24.78 g). The highest weight gain rate and specific growth rate were observed in fish at 20‰ (442.50% and 4.02%, respectively), alongside a significantly lower FCR (2.05) than in the 30‰ (2.37), 10‰ (2.17), and 0‰ (2.44) treatments. Based on these findings, a 20‰ salinity level is recommended for nursing juvenile L. argentimaculatus in cultivation systems.